KRITIK SOSIAL TERHADAP AKSI DEMONSTRASI PADA CERPEN “MAHASISWA TIO” KARYA ARIE MP TAMBA - Niken Oktaviani; Nurul Janah; Disti Erliani (Dharmas Education Journal (DE_Journal), 2024)
This study aims to identify and describe forms of social criticism in the short story “Mahasiswa Tio” by Arie MP Tamba using a sociological approach to literature. The method employed is a descriptive qualitative method, with the short story text serving as the data source, analyzed through the techniques of reading, note-taking, and data classification. The results of the study indicate that the short story contains several forms of social criticism, namely (1) criticism of student demonstrations as a form of resistance against a corrupt government, (2) criticism of opportunistic and greedy behavior among the public during chaotic situations, and (3) criticism of the violent consequences arising from demonstrations, such as the loss of life among students and the general public. These findings demonstrate that literary works can serve as a medium for social reflection that depicts societal realities and acts as a vehicle for criticism of social and political conditions. These findings indicate that literary works can serve as a medium for social reflection that portrays societal realities and acts as a vehicle for critiquing social and political cond